Vacuum drying of rosehip leathers: Modelling of coupled moisture content and temperature curves as a function of time with simultaneous time-varying ascorbic acid retention - Demarchi, Silvana María (2018)
Vacuum drying kinetics, thermal histories and quality kinetics of two rosehip leather formulations were determined, at tray temperatures between 40 and 70ºC. Data was simultaneously modelled as an ordinary differential equations system encompassing a transient water balance, a transient energy balance, and a variable-order quality kinetics equation, coupled to heat and mass transfer. A set of parameters was fitted for each formulation and satisfactory representations of the experimental data were obtained. Differences in drying rate compensated for the effect of the tray temperature on quality loss, so vacuum drying at 70 ºC was recommended for rosehip leathers due to the shorter drying time required. In particular, the reaction order for ascorbic acid degradation was found to be dependent on the tray temperature.